Ethanol Disrupts Reactivated Contextual Conditioned Fear Memory: Behavioral and Histological Perspectives - Alijan-pour, Jafar (Royan Institute, 2012)
OBJECTIVE: This research study is an attempt to examine whether the administration of ethanol after memory reactivation would modulate subsequent expression of memory in rats. Additionally, we examined whether this administration alters the density of Cornu Ammonis (CA)1 and CA3 pyramidal and dentate gyrus (DG) granule cells. MATERIALS AND METHODS: In this experimental study, adult male Wistar rats (200-300 g) were trained in a fear conditioning system using two 1 second, 0.6 mA shocks with an interval of 180 seconds. Twenty four hours later rats were returned to the chamber for 120 seconds. Immediately after reactivation they were injected with ethanol (0.5, 1, 1.5 mg/ kg) or saline. 1, 7 and 14 days after reactivation, rats were returned to the context for 5 minutes. Seconds of freezing (absence of all movement except respiration) were scored. In the second experiment (described in the previous paragraph), after test 1, animals were anesthetized with sodium pentobarbital and perfused transcardially with phosphate buffer (10 minutes) and 4% paraformaldehyde (15 minutes). The brains were postfixed in phosphate-buffered 4% paraformaldehyde (24 hours) and 30% sucrose. 10-µm sections were stained with cresyl violet. Data were analyzed by 1-and 2-way ANOVA for repeated measurements by means of SPSS 16.0. Tukey's post hoc test was performed to determine the source of detected significant differences. P <0 .05 were considered significant. Data are presented as mean ± SEM. RESULTS: Findings from the first experiment indicated that ethanol at a dose of 1.5 mg/kg significantly impaired recall of memory only in the first test. The density of CA1 and CA3 pyramidal and DG granule cells in the ethanol group was decreased (p< 0.01) compared with control group respectively 43.7%, 35.8%, and 37.8. CONCLUSION: The data demonstrate that ethanol exposure impairs post retrieval processes. Moreover, ethanol decreases the density of CA1, CA3 and DG cells. Presumably it would be a correlation between our behavioral and histological results.